Protective effect of chrysophanol on canine renal cell injury induced by canine parvovirus: Chrysophanol protects canine renal cells damaged by canine parvovirus - Gong, Ting (Cellular and Molecular Biology, 2023)
Canine parvovirus (CPV) causes apoptosis of canine kidney cells. As a polyphenol compound, chrysophanol (CHR) has antioxidant effects. However, it is not yet clear whether CHR has a protective effect on CPV-induced renal cell damage. In order to clarify the role of CHR in the lesion caused by CPV, this study constructed a model of Madin Darby Canine Kidney (MDCK) cell line injured by CPV in vitro and evaluated the effect of chrysophanol on the oxidative stress, expression of inflammatory cytokines and apoptosis of renal cell line induced by CPV through biochemical analysis, flow cytometry and real-time fluorescence quantitative polymerase chain reaction (RT-PCR). In this study, it has found that Pre-treatment with 40 μM CHR inhibited cell viability and the release of lactate dehydrogenase (LDH) of MDCK cells, and induced a decrease in malondialdehyde (MDA) content, reactive oxygen species (ROS) level, and expression of pro-inflammatory factors IL-6 and TNF-α. Besides, A reduction in mitochondrial membrane potential (ΔΨ), activities of Caspase-9 and Caspase-3 and apoptosis rate of CPV-infected MDCK cells which were pre-treated with CHR was observed. Therefore, CHR has a protective effect on renal cells caused by CPV and is closely related to depressing oxidative stress, inflammatory responses, and apoptosis, revealing that CHR is a potential cellular protective compound to combat viral infection.